Resistance Profile Antibiotics Pathogenic Bacteria from SWAB Wounds of Pontianak City Diabetes Treatment Clinic Patients - azura, Azura; Sri Tumpuk; Ari Nuswantoro (Sean Institute, 2023)
Diabetes mellitus (DM) is a type of metabolic disorder where the sufferer has high blood sugar levels due to the body's failure to respond or produces insufficient amounts of insulin, or a metabolic disorder caused by hyperglycemia due to abnormalities in insulin secretion and insulin action or both. One of the complications of diabetes is ulcers, where a superficial infection occurs on the sufferer's skin and becomes a strategic location for bacterial growth. Most of the drugs that are widely used to inhibit or kill bacteria that cause infections in humans are antibiotics which carry the risk of drug resistance. Antibiotic resistance is a growing problem in many parts of the world. Antibiotic resistance can occur due to inappropriate or excessive use of antibiotics. This study aims to determine the susceptibility of pathogenic bacteria to several antimicrobial agents or antibiotics and to determine the percentage of antibiotic resistance in diabetes mellitus patients who experience complications, which will make it easier to choose the right antibiotic for healing. This research uses a descriptive method using samples of bacterial isolates which have been identified as 11 samples of Staphylococcus aureus bacterial isolates, 11 samples of Pseudomonas aeruginosa isolates and 39 samples of Klebsiella pneumoniae bacterial isolates. Antimicrobial susceptibility test (AST) disk diffusion method (Kirby & Bauer test) using Mueller Hinton media. With eight different types of antibiotics, this test was carried out to prove antimicrobial activity by measuring the diameter of the antimicrobial activity inhibition zone. Resistance test results were obtained in Staphylococcus aureus experiencing the highest resistance to the antibiotic Gentamycin (CN) at 63.63%, in Pseudomonas aeruginosa experiencing high resistance to the antibiotic Ampicillin (AMP) at 54.54%, and in Klebsiella pneumoniae experiencing the highest resistance. against the antibiotic Ampicillin (AMP) was 41.02%. Preventing antibiotic resistance in wound healing is very important to ensure antibiotics remain effective in treating infections. Therefore, this research was carried out in order to determine the correct type of antibiotic for healing wounds in diabetes mellitus sufferers.